2013
DOI: 10.5194/bg-10-5967-2013
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Controlled experimental aquarium system for multi-stressor investigation of carbonate chemistry, oxygen saturation, and temperature

Abstract: As the field of ocean acidification has grown, researchers have increasingly turned to laboratory experiments to understand the impacts of increased CO2 on marine organisms. However, other changes such as ocean warming and deoxygenation are occurring concurrently with the increasing CO2 concentrations, complicating the understanding of the impacts of anthropogenic changes on organisms. This experimental aquarium design allows for independent regulation of CO2 concentration, O Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…For example, organisms in the CCLME will face changes in exposures to both the severity and frequency of low pH and saturation state conditions (Hauri et al, 2013), with impacts that can interact with exposures to declining oxygen concentrations (Rykaczewski andDunne 2010, Cocco et al, 2012). While capacity for resolving mean state vs. variability impacts and interactions between multiple stressors remains a limiting factor in the field, development of new experimental systems (Bockmon et al, 2013) can enable experimental treatments that mimic exposure regimes that organisms are observed and forecasted to face in situ. Such advances will be crucial to making more robust forecasts regarding the ecological consequences of future ocean change (Boyd, 2011;Harvey et al, 2013).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, organisms in the CCLME will face changes in exposures to both the severity and frequency of low pH and saturation state conditions (Hauri et al, 2013), with impacts that can interact with exposures to declining oxygen concentrations (Rykaczewski andDunne 2010, Cocco et al, 2012). While capacity for resolving mean state vs. variability impacts and interactions between multiple stressors remains a limiting factor in the field, development of new experimental systems (Bockmon et al, 2013) can enable experimental treatments that mimic exposure regimes that organisms are observed and forecasted to face in situ. Such advances will be crucial to making more robust forecasts regarding the ecological consequences of future ocean change (Boyd, 2011;Harvey et al, 2013).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…For coastal regions, the scientific community is just now assessing the longer-term variability in pH. Recent analyses of long-term data sets indicate that pH is changing rapidly in coastal Washington (Wootton and Pfister, 2012), in coastal upwelling zones along the US Pacific coast (Harris et al, 2013;Chan et al, 2014), at a coastal region in the Netherlands (Provoost et al, 2010), and in the Monterey Bay area where low pH water is associated with low oxygen water masses that reach the shallow, nearshore regions (Booth et al, 2012). Cruise data have provided snapshots of carbonate chemistry along the coast of the CCLME (Feely et al, 2008), and suggested that at some locations in northern California, undersaturated waters shoaled in the inner shelf.…”
mentioning
confidence: 99%
“…Several step-wise changes in the system level setting were conducted during the course of each experiment to maintain stable environmental conditions [67], and thus, data were not normally distributed. Treatment conditions were distinct for each experiment with respect to pH, Ω aragonite and [O 2 ], but not for temperature and alkalinity (Wilcoxon test; Table 1).…”
Section: System Overview and Experimental Treatmentsmentioning
confidence: 99%
“…The performance assessment presented in this study attests to the suitability and reliability of this system to meet the current needs of environmental laboratory research on jellyfish polyps, taking advantage of the benefits of working in a continuous flow system. This prototype adds to the current pool of newly designed devices (e.g., Fangue et al 2010;McGraw et al 2010;Bockmon et al 2013;Hoffmann et al 2013) aimed at providing better tools for testing the effects of acidification and other environmental stressors in marine organisms, a discipline that has recently been identified as research front number one in Ecology and Environmental Sciences (King and Pendlebury 2013).…”
Section: Discussionmentioning
confidence: 99%